1998
DOI: 10.1111/j.1745-4603.1998.tb00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Sensory and Instrumental Measurements for Mealiness Assessment in Apples. A Collaborative Test

Abstract: Definition and establishment of assessment procedures for mealiness of apple fruits using sensory and instrumental measurements were performed on ‘Boskoop', ‘Cox's Orange Pippin’ and ‘Jonagold’ samples with varying degrees of mealiness. The sensory procedure profiled mealiness as a loss of crispness, hardness, and juiciness, with an increase in the floury sensation in the mouth. High correlations between the sensory descriptors and instrumental parameters was shown through principal component analysis. The ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
60
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 9 publications
(4 reference statements)
3
60
0
3
Order By: Relevance
“…Within a wide project devoted to the study of mealiness in fruits, consumers perception and means for detection, several instrumental procedures have been tested for mealiness assessment [1]. In this sense, our laboratory has focused its aims in a first stage on performing instrumental tests for assessing some textural descriptors as crispiness, hardness and juiciness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within a wide project devoted to the study of mealiness in fruits, consumers perception and means for detection, several instrumental procedures have been tested for mealiness assessment [1]. In this sense, our laboratory has focused its aims in a first stage on performing instrumental tests for assessing some textural descriptors as crispiness, hardness and juiciness.…”
Section: Introductionmentioning
confidence: 99%
“…Mealiness is a negative attribute of sensory texture that combines the sensation of a desegregated tissue with the sensation of lack of juiciness [1]. Peach mealy textures are also known as woolliness and leatheriness.…”
Section: Introductionmentioning
confidence: 99%
“…Sensory analysis has shown that mealiness can be characterised by a combination of a lack of crispiness, a lack of juiciness and a lack of hardness (Barreiro et al, 1998b). Crispiness appears to be a characteristic which is lost soon after harvest, whereas hardness and juiciness decrease more gradually during storage.…”
Section: Introductionmentioning
confidence: 99%
“…The model explains the development of the hardness, tensile strength and juiciness of apple tissue. These mechanical parameters have been shown to be directly related to mealiness as perceived by sensory panels (Barreiro et al, 1998b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation